2021
DOI: 10.3389/fmicb.2021.726132
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Contributes to the Beneficial Effects of Bacillus subtilis PTA-271 and Trichoderma atroviride SC1 to Protect Grapevine Against Neofusicoccum parvum

Abstract: Grapevine trunk diseases (GTDs) are a big threat for global viticulture. Without effective chemicals, biocontrol strategies are developed as alternatives to better cope with environmental concerns. A combination of biological control agents (BCAs) could even improve sustainable disease management through complementary ways of protection. In this study, we evaluated the combination of Bacillus subtilis (Bs) PTA-271 and Trichoderma atroviride (Ta) SC1 for the protection of Chardonnay and Tempranillo rootlings ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 90 publications
(148 reference statements)
6
56
0
Order By: Relevance
“…has also been highlighted by Mutawila et al [52], probably related to the plant defense responses that differ between cultivars. These different defense responses to T. atroviride have been recently reported by Leal et al [62], where the authors observed that T. atroviride may act as a priming stimulus for Tempranillo plantlets, while no stimulus could be verified for Chardonnay. This is in agreement with our PCA analysis which showed a negative correlation among treatments with T. atroviride (Esquive), likely due to a difference of efficacy amongst cultivars, which reinforces the importance of the cultivar in wound colonization by Trichoderma spp.…”
Section: Efficacy Of Pruning Wound Protection Products Applied Alonesupporting
confidence: 66%
“…has also been highlighted by Mutawila et al [52], probably related to the plant defense responses that differ between cultivars. These different defense responses to T. atroviride have been recently reported by Leal et al [62], where the authors observed that T. atroviride may act as a priming stimulus for Tempranillo plantlets, while no stimulus could be verified for Chardonnay. This is in agreement with our PCA analysis which showed a negative correlation among treatments with T. atroviride (Esquive), likely due to a difference of efficacy amongst cultivars, which reinforces the importance of the cultivar in wound colonization by Trichoderma spp.…”
Section: Efficacy Of Pruning Wound Protection Products Applied Alonesupporting
confidence: 66%
“…Np-Bt67 induced severe apoplectic form of Botryosphaeria dieback and strong disease symptoms characterized by (i) large cankers, (ii) dead branches, and (iii) stem necrosis as already reported for this particular N. parvum isolate [ 15 , 18 ]. Np-B and its mutant NpB-UV9 were equally pathogenic, but less pathogenic to grapevine than Np-Bt67 (no dead branches, no apoplectic foliar symptoms, reduced stem necrosis, reduced cankers).…”
Section: Discussionsupporting
confidence: 68%
“…This up-regulation could contribute to (-)-terremutin detoxification. Now considering the phenylpropanoid pathway and derivatives, the fact that Botryosphaeriaceae are known to metabolize grapevine phytoalexins [ 19 ] suggests that the weak up-regulation of PAL and STS could only slightly benefit to the pathogen metabolism [ 15 ]. Phytoalexin production could also increase consecutively to a CHI downregulation, as observed in plantlets treated with (-)-terremutin and in infected cuttings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations